A Dilated Cardiomyopathy Revealing a Neuroblastoma: Which Link?. Issue 7 (October 2016) - Duhil de Bénazé, Gwenaelle; Iserin, Franck; Durand, Philippe; Schleiermacher, Gudrun; Orbach, Daniel
Abstract : Acute cardiac dysfunctions associated to neuroblastoma have rarely been reported. Cases already described are mainly related to high blood pressure, and rarely to an "acute catecholamine cardiomyopathy" more frequently found in adults with pheochromocytoma or secreting paraganglioma. We here report a case of an 8-month-old infant with severe acute cardiac failure with dilated cardiomyopathy and moderate ischemic myocardial signs, revealing a favorable histoprognosis neuroblastoma. After specific treatment, evolution was favorable, and cardiac function completely recovered. The association of reversible ischemic signs with high plasmatic level of catecholamines suggests the existence of a catecholamine-induced acute cardiac dysfunction which imitates a Tako-Tsubo syndrome in neuroblastoma.